Beyond Constraining and Enabling: Toward New Microfoundations for Institutional Theory - Cardinale, Ivano (Academy of Management Review, 2018)
In this article I argue that the quest to establish microfoundations for institutional theory is hindered by two assumptions on which it currently rests: that structure simply constrains and enables action and that agency is mostly associated with reflexivity. I unpack these two assumptions and propose alternative microfoundations on which (1) structure not only constrains and enables action but also actively orients it toward some possibilities over others, and (2) the pre-reflective dimension of agency is explicitly theorized. It thus becomes possible to bridge long-standing divides within institutional theory, opening up avenues for further developing its microfoundations.